Sedimentology of Coal Conglomerate Deposits within Channel Facies in Samarinda Region, East Kalimantan, Indonesia - Herman Darman; Yahdi Zaim (Berita Sedimentologi, 1997)
Conglomerate beds with generally rounded to subrounded coal fragments are common in channel deposit facies in Samarinda Region (East Kalimantan), beds occur as interbeds within Balikpapan Formation. The coal fragments are possible transported and sedimented wood cuts or transported coal fragments from an older coal seam. This study compares the bed thickness with the diameter of the coal fragments and the other fragments. The cross plot of the bed thickness and grain size gives a better understanding of the sedimentation processes. Anomaly diameter of the coal fragments indicated wood fragments origin coals, also showed by the texture, the gradual changes of colour and the shape of the fragments. Small fragments (less than 1 cm) is hard to distinguish due to unclear texture and shape. There are two possibilities of the small coal fragments origins, coal clastics or small high density wood cuts. Coal fragments characteristics in conglomerate beds and typical Gp and Sp facies characteristics show that the coal fragment were deposited in a point bar controlled by a flooding process and the Gms facies was deposited in proximal channels.